Imobilização de Lipase A de Candida antarctica em nanocompósitos de argila modificada - Cavalcante, Antônio Luthierre Gama (2022)
Biocatalysis is a comprehensive area that has numerous applications in various fields as an alternative to chemical catalysis, highlighting industries: cosmetic, food, pharmaceutical and chemical. The use of commercial enzymes is recurrent in these industrial processes, however the high cost, the difficulty of reuse and recycling make their application economically unfeasible. In this sense, the enzymatic immobilization process on solid supports is an area of biocatalysis and allows enzymes to be recycled and reused more easily in various reactions, generally improving their physicochemical characteristics and minimizing costs. In this sense, the immobilization of Candida antarctica lipase A (CALA) via covalent interaction in functionalized kaolin (K) was proposed. The main aim of this work was to optimize the immobilization process by covalent bonding of Lipase A Candida antarctica in kaolin functionalized with carboxymethylcellulose (CMC) and branched polyethylenimine (BPEI) and activated with glutaraldehyde (GLU) and apply this biocatalyst (K@CMC-BPEI -GLU-CAL-A) in high industrial value reactions. The Taguchi method was used as a statistical tool to optimize the immobilization process, obtaining in the best reactional condition values of recovered activity, immobilization yield and derivative activity: 69.72 ± 1.3 %, 97.38 ± 1.7 % and 427.51 ± 5.3 U/g respectively. It is noteworthy that the immobilization time and enzyme load were the most significant parameters for the protocol. The biocatalyst formed and optimized was characterized by X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (EITF), Thermogravimetry (TGA) and Scanning Electron Microscopy (SEM), indicating the functionalization of kaolin and the immobilization of CAL -A on the surface of the support. In the range of 50 – 80°C, K@CMC-BPEI-GLUCAL-A showed a half-life 2-3 times longer than that of soluble CAL-A. Furthermore, it showed a 27% increase in initial activity at pH 9 and maintained 94 % of its initial activity after 90 days of storage. In silico studies showed that the immobilization of CAL-A on the support surface is favorable, as it has a binding affinity for the protein-anchored ligand, estimated at -4.3 to -3.7 kcal / mol. Therefore, experiments were carried out to verify the catalytic potential of the compound formed in the kinetic resolution of rac-1-(triisopropylsilyl)penta-1,4-diin-3-ol in organic medium via acylation. All of them yielded the product ((R)-1-Ac) with excellent enantiomeric excess (ee >99%) and enantioselectivity (E >200). In summary, the biocatalyst produced was optimized, improved its immobilization parameters and showed to be efficient in the kinetic resolution via acylation of a racemic mixture of a propargyl alcohol.